2017
DOI: 10.1016/j.jval.2017.08.1495
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness Analysis Of Two Long-Acting Muscarinic Antagonists For Copd Treatment In Spain: Umeclidinium VS. Tiotropium (HO-17-18472)

Abstract: analysis was based on a head-to-head trial comparing changes from baseline in lung function (FEV1) between umeclidinium 62.5mcg and tiotropium 18mcg, on a 12-week-period (Feldman G. et al. Int J Chron Obstruct Pulmon Dis 2016). A previously published linked equations cohort model, based on ECLIPSE and TORCH studies, which estimates COPD progression, exacerbation rates, associated healthcare-costs, quality-adjusted-life-years (QALYs) and survival, was used (Miravitlles M. et al. Int J Chron Obstruct Pulmon Dis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Several cost-effectiveness analyses have been conducted from a Spanish National Healthcare System perspective, using direct head-to-head data. One study compared UMEC and TIO [ 50 ], using direct head-to-head data from a 12-week study whereby in which UMEC was found to be superior to TIO for trough FEV 1 in the ITT population (treatment difference: 53 mL, 95% CI: 25, 81 mL; p < 0.001) [ 24 ]. Results from this cost-effectiveness analysis using direct head-to-head data from the UMEC and TIO study showed results comparable to our study, whereby UMEC dominated TIO, gaining similar 0.014 QALYs and demonstrating cost savings of €192 [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several cost-effectiveness analyses have been conducted from a Spanish National Healthcare System perspective, using direct head-to-head data. One study compared UMEC and TIO [ 50 ], using direct head-to-head data from a 12-week study whereby in which UMEC was found to be superior to TIO for trough FEV 1 in the ITT population (treatment difference: 53 mL, 95% CI: 25, 81 mL; p < 0.001) [ 24 ]. Results from this cost-effectiveness analysis using direct head-to-head data from the UMEC and TIO study showed results comparable to our study, whereby UMEC dominated TIO, gaining similar 0.014 QALYs and demonstrating cost savings of €192 [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…One study compared UMEC and TIO [ 50 ], using direct head-to-head data from a 12-week study whereby in which UMEC was found to be superior to TIO for trough FEV 1 in the ITT population (treatment difference: 53 mL, 95% CI: 25, 81 mL; p < 0.001) [ 24 ]. Results from this cost-effectiveness analysis using direct head-to-head data from the UMEC and TIO study showed results comparable to our study, whereby UMEC dominated TIO, gaining similar 0.014 QALYs and demonstrating cost savings of €192 [ 50 ]. Another Spanish cost-effectiveness analysis of UMEC/VI versus TIO alone estimated 3-year costs of €6215 and QALYs of 2.025 for patients treated with UMEC/VI and found UMEC/VI to be more effective and costlier than TIO monotherapy, with an incremental cost-effectiveness ratio (ICER) of €21,475/QALY [ 26 ].…”
Section: Discussionmentioning
confidence: 99%